Plasma Biomarkers of Neuropathogenesis in Hospitalized Patients With COVID-19 and Those With Postacute Sequelae of SARS-CoV-2 Infection. Issue 3 (7th May 2022) - Hanson, Barbara A.; Visvabharathy, Lavanya; Ali, Sareen T.; Kang, Anthony K.; Patel, Tulsi R.; Clark, Jeffrey R.; Lim, Patrick H.; Orban, Zachary S.; Hwang, Soyoon S.; Mattoon, Dawn; Batra, Ayush; Liotta, Eric M.; et al.
Abstract : Background and Objectives: Although patients hospitalized with COVID-19 frequently present with encephalopathy, those with mild initial COVID-19 disease who never required hospitalization also often develop neurologic symptoms as part of postacute sequelae of severe acute respiratory coronavirus type 2 (SARS-CoV-2) infection (neuro-PASC). The pathogenic mechanisms of COVID-19 encephalopathy and neuro-PASC are unknown. We sought to establish biochemical evidence of CNS injury in those patients and their association with neuropsychiatric manifestations and SARS-CoV-2 antigenemia. Methods: We recruited hospitalized, posthospitalized, and nonhospitalized patients with confirmed diagnosis of COVID-19 with neurologic symptoms in addition to healthy control (HC) subjects. Plasma neurofilament light chain (pNfL), plasma glial fibrillary acidic protein (pGFAP), and plasma SARS-CoV-2 Nucleocapsid antigen (pN Ag) were measured by HD-X Simoa analyzer (Quanterix) and compared with neuropsychiatric symptoms, patient-reported quality-of-life measures, and standardized cognitive assessments. Neuroglial scores (pGFAP/pNfL) were calculated to estimate the relative contribution of astroglial and neuronal involvement. Results: We enrolled a total of 64 study participants, including 9 hospitalized patients with COVID-19 encephalopathy (CE), 9 posthospitalization neuro-PASC (PNP) patients, 38 nonhospitalized neuro-PASC (NNP) patients, and 8 HC subjects. Patients with CE were older, had higher pNfL and pGFAP concentrations, and more frequent pN Ag detection than all neuro-PASC groups. PNP and NNP patients exhibited similar PASC symptoms, decreased quality-of-life measures, and cognitive dysfunction, and 1 of the 38 (2.6%) NNP patients had pN Ag detectable 3 weeks postsymptoms onset. Patients with neuro-PASC presenting with anxiety/depression had higher neuroglial scores, which were correlated with increased anxiety on quality-of-life measures. Discussion: pNfL, pGFAP, and pN Ag measurements indicate neuronal dysfunction and systemic involvement in hospitalized COVID-19 patients with encephalopathy. Detection of SARS-CoV-2 N Ag in blood 3 weeks after symptoms onset in a nonhospitalized patient suggests that prolonged antigenic stimulation, or possibly latent infection, may occur. Anxiety was associated with evidence of astroglial activation in patients with neuro-PASC. These data shed new light on SARS-Cov-2 neuropathogenesis and demonstrate the value of plasma biomarkers across the COVID-19 disease spectrum.